2014
DOI: 10.1371/journal.pone.0092647
|View full text |Cite
|
Sign up to set email alerts
|

Pemt Deficiency Ameliorates Endoplasmic Reticulum Stress in Diabetic Nephropathy

Abstract: Phosphatidylethanolamine N-methyltransferase (Pemt) catalyzes the methylation of phosphatidylethanolamine (PE) to phosphatidylcholine (PC) mainly in the liver. Under an obese state, the upregulation of Pemt induces endoplasmic reticulum (ER) stress by increasing the PC/PE ratio in the liver. We targeted the Pemt gene in mice to explore the therapeutic impact of Pemt on the progression of diabetic nephropathy and diabetes, which was induced by the injection of streptozotocin (STZ). Although the blood glucose le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Although PEMT is predominantly found in the liver, we have detected PEMT protein in other tissues, such as adipose and testis (2). Others have reported PEMT protein in kidneys; however, we could not reproduce this result using our in-house developed antibody (2,15). We hypothesized that the phenotype observed in HFD-fed Pemt 2/2 mice is dependent upon hepatic PEMT activity.…”
Section: Metabolic Benefits Of Pemt Deficiency Is Mediated Through Hementioning
confidence: 70%
See 1 more Smart Citation
“…Although PEMT is predominantly found in the liver, we have detected PEMT protein in other tissues, such as adipose and testis (2). Others have reported PEMT protein in kidneys; however, we could not reproduce this result using our in-house developed antibody (2,15). We hypothesized that the phenotype observed in HFD-fed Pemt 2/2 mice is dependent upon hepatic PEMT activity.…”
Section: Metabolic Benefits Of Pemt Deficiency Is Mediated Through Hementioning
confidence: 70%
“…Our lab has previously shown that whole-body PEMTknockout mice are protected against DIO and IR (3). Because PEMT protein has been found in other tissues such as white adipose tissue and testis, we aimed to delineate the role of PEMT, specifically in the liver, in weight gain and IR (2,15). We restored hepatic PEMT in Pemt 2/2 mice by AAV-mediated expression.…”
Section: Hepatic Pemt Deficiency Protects Against Diomentioning
confidence: 99%
“…The conversion of PE to PC is catalyzed by phosphatidylethanolamine N-methyltransferase (Pemt). Glomerular hypertrophy and albuminuria have been shown to be significantly attenuated in Pemt-deficient mice as a result of a decrease in the ratio of PC/PE and alleviation of ER stress (28). Interestingly, although most phospholipids declined, a specific side chain, 36:1, was increased in almost every phospholipid, including PE, PI, PA, PG PC, and PS.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple apoptosis pathways have been implicated in tubular atrophy, including recent reports linking proximal tubule endoplasmic reticulum (ER) stress in diabetic nephropathy [29, 30]. Until recently the most compelling argument that apoptosis is the cause of tubular atrophy had been kinetic experiments demonstrating that proximal tubule apoptosis precedes tubular atrophy in mouse models of focal and segmental glomerulosclerosis (FSGS) [22].…”
Section: Mechanisms Of Tubular Atrophymentioning
confidence: 99%